41.1: Development of RGBw LCD with Edge Lit 2D Local Dimming System for Automotive Applications. Issue 1 (June 2015) - Takasaki, Naoyuki; Harada, Tsutomu; Sakaigawa, Akira; Sako, Kazuhiko; Mifune, Masayuki; Shiraishi, Yasuhisa
Abstract : We have developed 10‐inch RGBW LCD with edge‐lit 2D local dimming backlight system for automotive applications. This prototype system has power consumption reduction performance of 41.5% compared to a conventional RGB display without local dimming backlight. The performance and evaluation results are described in this paper.